Meat consumption and risk of ischemic heart disease: A systematic review and meta-analysis. Issue 3 (25th January 2023) - Papier, Keren; Knuppel, Anika; Syam, Nandana; Jebb, Susan A.; Key, Tim J.
Abstract: There is uncertainty regarding the association between unprocessed red and processed meat consumption and the risk of ischemic heart disease (IHD), and little is known regarding the association with poultry intake. The aim of this systematic review and meta-analysis was to quantitatively assess the associations of unprocessed red, processed meat, and poultry intake and risk of IHD in published prospective studies. We systematically searched CAB Abstract, MEDLINE, EMBASE, Web of Science, bioRxiv and medRxiv, and reference lists of selected studies and previous systematic reviews up to June 4, 2021. All prospective cohort studies that assessed associations between 1(+) meat types and IHD risk (incidence and/or death) were selected. The meta-analysis was conducted using fixed-effects models. Thirteen published articles were included (ntotal = 1, 427, 989; ncases = 32, 630). Higher consumption of unprocessed red meat was associated with a 9% (relative risk (RR) per 50 g/day higher intake, 1.09; 95% confidence intervals (CI), 1.06 to 1.12; nstudies = 12) and processed meat intake with an 18% higher risk of IHD (1.18; 95% CI, 1.12 to 1.25; nstudies = 10). There was no association with poultry intake (nstudies = 10). This study provides substantial evidence that unprocessed red and processed meat, though not poultry, might be risk factors for IHD.